SPC Liposomes as Possible Delivery Systems for Improving Bioavailability of the Natural Sesquiterpene β-Caryophyllene: Lamellarity and Drug-Loading as Key Features for a Rational Drug Delivery Design - Antonella Di Sotto; Patrizia Paolicelli; Martina Nardoni; Lorena Abete; Stefania Garzoli; Silvia Di Giacomo; Gabriela Mazzanti; Maria Antonietta Casadei; Stefania Petralito (MDPI AG, 2018)
The natural sesquiterpene β-caryophyllene (CRY) has been highlighted to possess interesting pharmacological potentials, particularly due to its chemopreventive and analgesic properties. However, the poor solubility of this sesquiterpene in aqueous fluids can hinder its uptake into cells, resulting in inconstant responses of biological systems, thus limiting its application. Therefore, identifying a suitable pharmaceutical form for increasing CRY bioavailability represents an important requirement for exploiting its pharmacological potential. In the present study, the ability of soybean phosphatidylcholine (SPC) liposomes to improve bioavailability and absorption of CRY in cancer cells has been evaluated. Liposomal formulations of CRY, differing for lamellarity (i.e., unilamellar and multilamellar vesicles or ULV and MLV) and for the drug loading (i.e., 1:0.1, 1:0.3 and 1:0.5 mol/mol between SPC and CRY) were designed with the aim of maximizing CRY amount in the liposome bilayer, while avoiding its leakage during storage. The low-loaded formulations significantly potentiated the antiproliferative activity of CRY in both HepG2 and MDA-MB-468 cells, reaching a maximum IC50 lowering (from two to five folds) with 1:0.3 and 1:0.1 SPC/CRY MLV. Conversely, increasing liposome drug-loading reduced the ability for CRY release, likely due to a possible interaction between SPC and CRY that affects the membrane properties, as confirmed by physical measures.